Why history? a history - Bloxham, Donald 1973- (Oxford scholarship online, 2020)
What is the point of history? Why has the study of the past been so important for so long? Why History? A History contemplates two and a half thousand years of historianship to establish how very different thinkers in diverse contexts have conceived their activities, and to illustrate the purposes that their historical investigations have served. At the core of this work, whether it is addressing Herodotus, medieval religious exegesis, or twentieth-century cultural history, is the way that the present has been conceived to relate to the past. Alongside many changes in technique and philosophy, Donald Bloxham's book reveals striking long-term continuities in justifications for the discipline